Pengaruh Komposit Hibrid Serat Batang Pisang Dan Serat Bambu Dengan Perlakuan Asap Cair Untuk Mengetahui Nilai Impak - Rizki, Muhammad; Masdani, Masdani; Sugiyarto, Sugiyarto (Jurnal Inovasi Teknologi Terapan, 2025)
Every year, technological development continues to progress at a rapid pace. Today's technology is developed through various new innovations, due to the increasing use of metals, the availability of natural resources is decreasing. Therefore, replacement materials that are environmentally friendly and renewable are needed. An example of technology in the field of materials is composites that use natural fibers, such as banana stem fibers, and bamboo as reinforcement. The purpose of this study was to investigate the effect of variation in the volume fraction of hybrid composites on the impact strength of composite materials. The tests conducted followed the ISO 179-1 standard. The analysis was conducted using the experiment method. This study used variations in the volume fraction of kepok banana stem fiber and bamboo fiber, namely 10%: 20%, 15% : 15%, and 20%: 10%. Duration of liquid smoke soaking for 2 hours. The average value of the impact test is highest in the composition of kepok banana stem fiber: 10% bamboo fiber: 20%, with an average of 134.2 kJ/m2. Meanwhile, the lowest impact test value was in the composition of kepok banana stem fiber: 20% bamboo fiber: 10%, with an average value of 62.9 kJ/m2.